Until Love Do Us Part: Counter-Narrative as a Narrative Instrument. A Theoretical Approach - Sarasqueta, Gonzalo (2024)
The purpose of this paper is to provide a theoretical approach to the notion of political counter-narrative. Given the novelty of this narrative technique, its causes are first addressed: moral absolutism, affective polarization, informational chaos, uncertainty, and digital tribalism. Then, the counter-narrative is defined as a semantic structure that, regardless of temporality, seeks to destroy the symbolic capital of the adversary. Subsequently, its main features –reactivity, negativity, emotiveness, stereotyping, and permanence– are detailed, as are its functions –linking wills through opposition, drawing clear identity boundaries, being emotionally rewarding, and simplifying reality–. In closing, a review of the main findings is provided, and various lines of research are proposed, such as observing the resonance and application of this technique by citizens and the possibility of conducting a comparative analysis, through practical cases, between the counter-narrative and its nemesis, political narrative.